A role for universal pension? Simulating universal pensions in Ecuador, Ghana, Tanzania, and South Africa - Maria Joust; Pia Rattenhuber (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
We use four novel, cross-country comparable tax-benefit microsimulation models for Ecuador, Ghana, Tanzania, and South Africa to evaluate ex ante the expansion of a universal oldage pension in a static setting. Universal pensions would significantly reduce poverty and inequality in settings in which no means-tested old-age pensions exist (such as Ghana and Tanzania). If means-tested old-age pensions exist and shall be maintained, universal pensions as a top-up scheme only make a difference for the income distribution if the existing schemes do not reach the entire vulnerable population, such as in Ecuador. Costs for the proposed schemes are substantial.
Keywords: H55; I32; C15; 330; old-age benefit; poverty; SOUTHMOD; tax-benefit microsimulation